GlobalSCAPE: successes and failures in connecting with science communicators around the world - Hurley, Mairad; Roche, Joseph; Taylor, Aoife (My University, 2024)
The GlobalSCAPE research project was tasked with engaging people working in science communication to better understand their views of the field. While being a European-based research project, GlobalSCAPE aimed to connect with science communicators across the globe. This practice insight paper reflects on the lessons learned from GlobalSCAPE, the successes and failures, and what might be done to continue the work of global science communication research projects. It is hoped that such learnings will be of broad interest to research and practice communities grappling with ways to fund and support science communication around the world.
PUBLISHED
Keywords: Professionalism, professional development and training in science communication; Professionalism, professional development and teaching in science communication; Science communication in the developing world; Inclusive Society; SCIENCE COMMUNICATION; Science & Society